Relevance of Criminal Profiling in Criminal Justice System in Benue State Nigeria - Tanko Shawulu Paul; Dominic Aondona Iornumbe (Jurnal Restorasi : Hukum dan Politik, 2025)
Since its inception, criminal profiling has evolved significantly, incorporating advancements in forensic science, psychology, and technology. Modern criminal profiling techniques involve a multidisciplinary approach, drawing upon various fields such as forensic psychology, geographic profiling, and crime scene reconstruction. Geographic profiling, for instance, utilizes spatial analysis and mapping techniques to identify potential areas where an offender may reside or operate, based on the locations of committed crimes). In Nigeria, the use of criminal profiling techniques has been gradually gaining traction, although its application remains limited in many regions). Benue, the capital city of Benue State, has witnessed a surge in criminal activities, including armed robbery, kidnapping, and violent crimes. These incidents have highlighted the need for more effective investigative methods, such as criminal profiling, to aid law enforcement agencies in identifying and apprehending offenders. Several factors contribute to the challenges faced in implementing criminal profiling in Benue state and other parts of Nigeria. Limited resources, inadequate training, and a lack of standardized procedures have hindered the widespread adoption of these techniques. Additionally, cultural and societal factors may influence the perception and acceptance of criminal profiling techniques, as some communities may view them as foreign or incompatible with traditional methods of investigation. Routine activity theory was adopted. Secondary data was used.